HUBUNGAN STRES, EMOTIONAL EATING, DAN AKTIVITAS FISIK DENGAN STATUS GIZI MAHASISWA TINGKAT AKHIR UNIVERSITAS UDAYANA - Kusumah, Rr. Tiara Santi; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Nutritional problems often occur in early adulthood. The eating patterns of young adults, particularly as university seniors, can be characterized by emotional eating, which is linked to increased stress and reduced physical activity. This research aims to investigate the relationship between stress, emotional eating, physical activity, and nutritional status among senior students at Udayana University. It is a quantitative cross-sectional study. Data were collected in March 2023 from a randomly selected sample of 145 senior students. Nutritional status data based on BMI, stress levels using the DASS questionnaire, emotional eating using DEBQ, and physical activity using IPAQ were analyzed using chi-square. The analysis results show that the majority of students have a normal nutritional status (65.3%). There is a significant relationship between stress (p = 0.003), emotional eating (p = 0.000), physical activity (p = 0.002), and the nutritional status of senior students at Udayana University. It is concluded that stress, emotional eating, and physical activity are significantly associated with nutritional status. It is recommended that students manage stress effectively, pay attention to their dietary intake, and maintain regular physical activity.   Keywords: S tress L evel, E motional E ating, and P hysical A ctivity L evel